Nutritional Status of Toddlers Aged 0-59 Months: a Descriptive Study - Fibrinika Tuta Setiani; Heny Lestari; Abdullah Azam Mustajab (International Journal of Health and Medicine, 2024)
toddlerhood is called the golden age where a person experiences rapid growth and development. However, in 2022 based on the results of the Indonesian Nutritional Status Survey (SSGI) showed that toddlers with stunting were 21.6%, toddlers with malnutrition were 7.7%, toddlers with undernutrition were 17.1% and toddlers who were obese were 3.5%. The purpose of this study was to describe the nutritional status of toddlers aged 0-59 years in Kedalon Village. The quantitative descriptive research method with observational analytics on data from nutritional status measurements in toddlers aged 0-59 years. The total sample was 192 toddlers in Kedalon Village, the data was subjected to descriptive analysis. The results of toddlers with normal height were 182 (94.79%), short height 7 (3.65%) and very short height toddlers 3 (1.56%). Toddlers with normal weight 164 (85.42%), underweight toddlers 18 (9.37%), overweight toddlers 7 (3.65%) and very underweight toddlers 3 (1.56%). Toddlers based on weight according to height with normal results 163 (84.90%), undernutrition 10 (5.21%), overnutrition 3 (1.56%) and obesity 2 (1,045) and severe malnutrition 2 (1.04%). Toddlers who are identified as having nutritional problems can be given adequate nutritional interventions so that growth and development problems do not occur in the future.